2010
DOI: 10.1097/bcr.0b013e3181d0f4bf
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Antibiotic Resistance Pattern of Metallo-β-Lactamase-Producing Pseudomonas aeruginosa From Burn Patients—Experience of an Indian Tertiary Care Hospital

Abstract: The objective of the study is to determine the prevalence of Pseudomonas aeruginosa from burn patients, antibiotic resistance pattern and occurrence of acquired MBL-producing P. aeruginosa among isolates collected from burn patients. In this study, two phenotypic methods were used for the detection of MBL-producing P. aeruginosa: zone enhancement with EDTA-impregnated imipenem and ceftazidime discs, and modified Hodge test. One hundred fifty-four isolates of P. aeruginosa were obtained from July 2007 to July 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 17 publications
1
16
0
1
Order By: Relevance
“…This is similar to the 28% reported by a previous study from the same city [8]. A higher prevalence has been reported by studies elsewhere, such as 57% in Iran [10], 55% in India [11] and 51% in Palestine [12]. This may be due the type inclusion criteria for the microorganisms accounted for and cultured.…”
supporting
confidence: 79%
“…This is similar to the 28% reported by a previous study from the same city [8]. A higher prevalence has been reported by studies elsewhere, such as 57% in Iran [10], 55% in India [11] and 51% in Palestine [12]. This may be due the type inclusion criteria for the microorganisms accounted for and cultured.…”
supporting
confidence: 79%
“…As shown in TABLE 5, 16 studies that investigated the activity of chloramphenicol against P. aeruginosa met our research criteria, with a mean susceptibility rate of 13% [101][102][103][104][105][106][107][108][109][110][111][112][113][114][115][116]. Eighty-seven percent of the studies were performed in developed countries.…”
Section: Pseudomonas Aeruginosamentioning
confidence: 99%
“…Agar dilution 23% meropenem-R 14 [108] 2008 UK 52 BSAC-DD -0 [109] 2009 India 20 KB -0 [110] 2009 Malaysia 48 KB 69% MDR (R ‡2 ATB) 40 [111] 2009 Australia 14 --0 [112] 2009 Brazil 10 KB -30 [113] 2010 India 25 -100% MBL 32 [114] 2011 Nigeria 15 KB -20 [115] 2012 China 14 --0 Antagonism [122] Inhibition of early (6 h) and late (20 h) bactericidal activity of ampicillin by chloramphenicol Ampicillin -21 enteric organisms, including Salmonella spp. and other Gram-negative bacilli…”
Section: Expert Commentarymentioning
confidence: 99%
“…Varsha Gupta, et al reported MBL production (84%), Bhale Rao, et al (67%) and 72% by Fereshteh shaheheraghi, et al [31,27,32]. 16% of the Imipenem resistant isolates were positive for MBL production in Rajput Anuradha, et al study [33]. MBL production was seen in 50% of Ps.…”
Section: Discussionmentioning
confidence: 99%